Peculiarities of ambulatory blood pressure monitoring in patients who have suffered from COVID-19 - V.O. Zbitnieva; O.B. Voloshyna; I.V. Balashova; E.A. Zubok; O.R. Dukova; L.I. Kovalchuk (Medičnì Perspektivi)
Violations of blood pressure control in patients who have had COVID-19 can be due to many pathophysiological factors. Further study of the features of blood pressure (BP) fluctuations in this category of patients will allow to diagnose arterial hypertension (AH) on time, to identify the uncontrolled course of AH and to select the optimal tactics of patients’ management. It was suggested to determine the characteristics of BP fluctuations in patients who have suffered from COVID-19 more than 12 weeks ago, based on the results of ambulatory (daily) blood pressure monitoring. 98 patients (51 men – 52.0%, 47 women – 47.9%) who have had COVID-19 infection more than 12 weeks ago were examined. Patients were divided into 2 groups – with and without a history of AH. The groups of examinees were homogeneous in age and gender. Ambulatory blood pressure monitoring (AM BP) was carried out on the CardioTens apparatus (Meditech, Hungary) according to the standard method. According to the data of AM BP in patients with AH in the anamnesis, who have suffered from COVID-19 more than 12 weeks ago, significantly higher average indicators of daily systolic blood pressure were recorded, and significant violations of the indicators of variability of systolic blood pressure during the day and night periods, pressure load during the day period, as well as a significantly higher degree and the rate of the morning rise in systolic blood pressure. In patients without a history of AH who have suffered from COVID-19 more than 12 weeks ago, in 21.4% cases there was newly diagnosed AH, in 33.3% of cases, increased variability of systolic blood pressure was observed, mainly during the day, in 21.4% of cases, the degree and speed of the morning rise of systolic blood pressure were increased, which indicated the presence of hypertensive reactions to household loads. In patients with a history of AH, in 55.3% of cases there was observed an increase in average blood pressure values per day, during the day and night periods, which was considered as ineffective blood pressure control and required an increase in the doses of previously prescribed antihypertensive drugs or the use of additional antihypertensive drugs in the treatment regimen. In patients with AH in the anamnesis, who have suffered from COVID-19 more than 12 weeks ago, reliable violations of many indicators of AM BP, deterioration of blood pressure control were recorded. In the patients, who did not have AH and who have suffered from COVID-19 more than 12 weeks ago, the presence of a hypertensive reaction to household loads and newly diagnosed AH were odserved.